The Effect of High Poly Unsaturated Fatty Acid (PUFA) Dietary Supplementation on Inflammatory Status of Patients with Advanced Cervical Cancer on Radiation Treatment - Sri Wuryanti; Andrijono Andrijono; Susworo Susworo; Fiastuti Witjaksono (Acta Medica Indonesiana)
Aim: to identify the effect of high-PUFA dietary supplementation on inflammatory status of patients with advanced cervical cancer. Methods: a randomized double-blind clinical trial was conducted in patients with advanced cervical cancer who had undergone external radiation therapy at Department of Radiotherapy, Cipto Mangunkusumo Hospital, Jakarta, between April 2013 and April 2014. The inflammatory status was evaluated based on serum prostaglandin E2 (PGE2) levels using ELISA method. The dietary supplementation was isocaloric, isoprotein and contained PUFA with a ratio of ω-6: ω-3 fatty acid = 1.27:1 and supplementation without PUFA. Data were analyzed with statistical tests, including Shapiro-Wilk test, independent T-test and Mann–Whitney test. Results: there was statistically no significant difference on PGE2 level between treatment and control groups (p=0.127). However, there was clinically significant difference, in which the treatment group had reduced PGE2 level by 8.9%; while the control group had increased level by 28.1%. Conclusion: dietary supplementation enriched with PUFA can reduce inflammatory status in patients with advanced cervical cancer. Reduced PGE2 level will lower the survival of cancer cells; therefore dietary supplementation enriched with PUFA with a ratio of ω-6 : ω-3 fatty acid = 1.27 : 1 along with radiation therapy may improve tumor response to radiation. Key words: cervical cancer, ω-3 PUFA, ω-6 PUFA, PGE2 level.